Expressive timing facilitates the neural processing of phrase boundaries in music: evidence from event-related potentials. - Eva Istók (Public Library of Science (PLoS), 2013)
The organization of sound into meaningful units is fundamental to the processing of auditory information such as speech and music. In expressive music performance, structural units or phrases may become particularly distinguishable through subtle timing variations highlighting musical phrase boundaries. As such, expressive timing may support the successful parsing of otherwise continuous musical material. By means of the event-related potential technique (ERP), we investigated whether expressive timing modulates the neural processing of musical phrases. Musicians and laymen listened to short atonal scale-like melodies that were presented either isochronously (deadpan) or with expressive timing cues emphasizing the melodies' two-phrase structure. Melodies were presented in an active and a passive condition. Expressive timing facilitated the processing of phrase boundaries as indicated by decreased N2b amplitude and enhanced P3a amplitude for target phrase boundaries and larger P2 amplitude for non-target boundaries. When timing cues were lacking, task demands increased especially for laymen as reflected by reduced P3a amplitude. In line, the N2b occurred earlier for musicians in both conditions indicating general faster target detection compared to laymen. Importantly, the elicitation of a P3a-like response to phrase boundaries marked by a pitch leap during passive exposure suggests that expressive timing information is automatically encoded and may lead to an involuntary allocation of attention towards significant events within a melody. We conclude that subtle timing variations in music performance prepare the listener for musical key events by directing and guiding attention towards their occurrences. That is, expressive timing facilitates the structuring and parsing of continuous musical material even when the auditory input is unattended.